Cephalometry without complex dedicated postprocessing in an oriented magnetic resonance imaging dataset: a pilot study. (18th March 2021) - März, Karoline; Chepura, Taras; Plewig, Blanka; Haddad, Daniel; Weber, Daniel; Schmid, Matthias; Hirschfelder, Ursula; Gölz, Lina
Summary: Objectives: Magnetic resonance imaging (MRI) enables a 3D-volume-imaging without ionizing radiation. Therefore, it was the aim of this study to present a post-processing-free method for cephalometric analysis of a MRI-dataset and to examine whether there is a significant difference between cephalometric analysis of conventional 2D cephalograms and MRI scans. Methods: One MRI scan each was performed on three cadaver heads using a 3T-MR-scanner. Cephalometric analysis was conducted directly on the 3D dataset. All reference points were projected onto a virtual sagittal plane that was perpendicular to the Frankfort horizontal plane. Double-sided points were averaged. Cephalometric angles were measured from the projected points. Results were compared with cephalometric measurements on conventional lateral cephalometric radiographs (LCRs). The cephalometric analysis was performed by five raters. Results: 390-angle measurements were obtained. The inter-rater reliability was high [intraclass correlation coefficients (ICCs) ≥ 0.74 for all angles]. Differences between the measurements on the cephalograms and MRI scans ranged between –0.91° (–1.88°, 0.07°) and 0.97° (–0.63°, 2.57°) on average and were equivalent with respect to a margin of [–2°, 2°] in all angles except L1—Me-Tgo (Bonferroni-Holm-corrected P < 0.05 in all angles except L1—Me-Tgo). The best match was found for the SNA angle. Conclusion: The clinical comparability of the MRI- and LCR-based cephalometry could be stated. Using MRI in orthodontics would reduce radiation exposure and the risk of stochastic radiation damage, which is of importance especially in younger patients.